2017
DOI: 10.1007/s10862-017-9630-x
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and Valid Coding of Thin Slices of Video Footage: Applicability to the Assessment of Mother-Child Interactions

Abstract: When using behavioral-observation methods for coding video footage, it is unknown how much time of an interaction needs to be coded to gain results that are representative for the behavior of interest. The current study examined this problem using the INTAKT, a standardized observational measure for assessing the quality of mother-child interactions. Results from coding only 10 min of each video (i.e., thin slices) were compared with results from coding the remaining parts (averaging about 40 min) of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In a similar study, acceptable levels of slice-whole validity was found for 5-min, and especially 10-min, slices extracted from motivational clinical interviews (a type of trained counseling style) in five of seven measured constructs (Klonek et al, 2015 ). And, importantly, the authors also investigated the location of extracted slices and found that 5-min slices extracted from after the first 5-min of the interaction had the strongest validity, supporting previous recommendations to avoid using slices from the very beginning of interactions (Murphy et al, 2015 ; Hirschmann et al, 2018 ).…”
Section: Comparative Thin-slice Researchsupporting
confidence: 67%
See 2 more Smart Citations
“…In a similar study, acceptable levels of slice-whole validity was found for 5-min, and especially 10-min, slices extracted from motivational clinical interviews (a type of trained counseling style) in five of seven measured constructs (Klonek et al, 2015 ). And, importantly, the authors also investigated the location of extracted slices and found that 5-min slices extracted from after the first 5-min of the interaction had the strongest validity, supporting previous recommendations to avoid using slices from the very beginning of interactions (Murphy et al, 2015 ; Hirschmann et al, 2018 ).…”
Section: Comparative Thin-slice Researchsupporting
confidence: 67%
“…The thin-slice measurement technique itself is applicable to any behavioral domain, potentially even for behavioral measurement of non-human populations (Jamieson et al, 2017 ). Perhaps an expanded view of what constitutes a “thin slice” (beyond 5 min) is warranted given research on longer slices (e.g., 10 min) from lengthier interactions (e.g., >40 min) that shows similarities to findings examining shorter slices from briefer interactions (e.g., 30 s from 5 min) (Caperton et al, 2018 ; Hirschmann et al, 2018 ). At a conceptual level, there is evidence that thin slices reliably and validly measure behavior across various domains, including zero-acquaintanceship interactions and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For maternal care, a second independent rater reexamined all video material. Intraclass correlation is an established statistical method to assess interrater differences of video material in subjective mother-infant relationships 60 . Only parameters showing an excellent inter-rater agreement 61 with r = > 0.75 were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the present within-studies analysis of the impact of slice length on predictive validity was undertaken. Researchers often have little guidance on which or how much behavior to select (e.g., Caperton, Atkins, & Imel, 2018; Hirschmann, Kastner-Koller, Deimann, Schmelzer, & Pietschnig, 2018; Lausberg & Sloetjes, 2016; Murphy et al, 2015). Previously, we demonstrated that thin slices of specific NVBs (most notably, interpersonal gazing) can reliably represent and predict longer behavioral streams (Murphy, 2005; Murphy et al, 2015).…”
mentioning
confidence: 99%